A comprehensive review of recent developments in falling-film, spray, bubble and microchannel absorbers for absorption systems. (May 2021) - Sehgal, Shitiz; Alvarado, Jorge L.; Hassan, Ibrahim G.; Kadam, Sambhaji T.
Abstract: Absorption refrigeration systems have been proposed as a reliable alternative to conventional vapor compression systems over the years. In the past, efforts have been made to comprehend the performance of absorption refrigeration systems based on thermodynamic analysis, experimentation and numerical simulations. However, absorption refrigeration systems are still not as efficient as vapor compression systems. Hence, the current review aims to highlight recent advances in the field of absorption refrigeration. Specifically, it covers recent development in the areas of falling-film, spray, bubble and microchannel absorbers. In the review, the roles of passive enhancement techniques including surface modifications, use of surfactants, and nanofluids used predominantly in falling film absorbers are discussed. Similarly, recent developments and findings in the study of bubble and spray absorbers are also presented in detail. Lastly, the review also covers recent developments in novel absorbers such as microchannel absorbers. Highlights: Comprehensive review of falling-film, spray, bubble and microchannel absorbers used in absorption systems. Absorption enhancement techniques, new configurations, and emerging trends for each absorber type. Novel absorber type including microchannel absorbers with simultaneous mass and heat transfer.